The fan and the female superhero in comic books. (1st September 2015) - Neumann, Caryn E.; Parks, Lori L.
Despite an increasing number of fangirls, female superheroes continue to represent the fears and concerns of male readers. These characters are not representative of girls or women despite their possession of a female form. Through the characterization and body shapes of male and female superheroes, the comics have remained focused upon fanboys. The female body in comics is not powerful but, instead, reinforces male dominance. While fangirls have made an effort to become a vocal force within comic book culture, the design of comic book content continues to marginalize girls and women.